The Limits of Linked Suppression for Regulatory T Cells - Ito, Toshiro; Yamada, Akira; Batal, Ibrahim; Yeung, Melissa Y.; McGrath, Martina M.; Sayegh, Mohamed H.; Chandraker, Anil; Ueno, Takuya (Frontiers in Immunology, 2016)
Background We have previously found that CD4+CD25+ regulatory T cells (Tregs) can adoptively transfer tolerance after its induction with costimulatory blockade in a mouse model of murine cardiac allograft transplantation. In these experiments, we tested an hypothesis with three components: (1) the Tregs that transfer tolerance have the capacity for linked suppression, (2) the determinants that stimulate the Tregs are expressed by the indirect pathway, and (3) the donor peptides contributing to these indirect determinants are derived from donor major histocompatibility complex (MHC) antigens (Ags). Methods First heart transplants were performed from the indicated donor strain to B10.D2 recipients along with costimulatory blockade treatment (250 μg i.p. injection of MR1 on day 0 and 250 μg i.p. injection of CTLA-4 Ig on day 2). At least 8 weeks later, a second heart transplant was performed to a new B10.D2 recipient who had been irradiated with 450 cGy. This recipient was given 40 × 106 naive B10.D2 spleen cells + 40 × 106 B10.D2 spleen cells from the first (tolerant) recipient. We performed three different types of heart transplants using various donors. Results (1) Tregs suppress the graft rejection in an Ag-specific manner. (2) Tregs generated in the face of MHC disparities suppress the rejection of grafts expressing third party MHC along with tolerant MHC. Conclusion The limits of linkage appear to be quantitative and not universally determined by either the indirect pathway or by peptides of donor MHC Ags.